Pengaruh Upah Minimum dan Inflasi Terhadap Jumlah Penduduk Miskin di Provinsi Jambi - Lili Andriani (Jurnal Ilmiah Dikdaya, 2019)
This study aims to determine the development and influence of minimum wages and inflation on the number of poor people in Jambi province in 2001-2015. The method used in this study is the multiple linear regression analysis method with the Ordinary Least Square (OLS) approach. The analytical tool used in this study was SPSS 23. In analyzing the factors that influence poverty in Jambi Province, the results show that the analysis for the analysis of the F test and the t test can be seen that the influence of the independent variable (Minimum Wage and Inflation) on the Number of Poor Populations in Jambi province simultaneously or together (F Test) affects the number of poor people. The calculated F value and F table 51.194> 3.89), with a significant level of 0.000 <0.05, there is a significant positive effect. For the t test of the minimum wage variable the value of t is calculated with t table of 7, 373> 2.170. The level of significance of the minimum wage variable (X1) is 0,000 <0.05 and for the t test of the inflation variable is 0.218 <2.17. The significant level of inflation variable (X2) is 0.831> 0.05.